2016
DOI: 10.1589/jpts.28.3316
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Japanese version of the selective control assessment of the lower extremity tool among patients with spastic cerebral palsy

Abstract: [Purpose] The aim of this study was to translate the Selective Control Assessment of the Lower Extremity (SCALE) tool from English to Japanese and to assess the reliability and validity of the Japanese version of the SCALE (SCALE-J) tool in Japanese patients with spastic cerebral palsy. [Subjects and Methods] The SCALE tool was translated into Japanese in accordance with the published guidelines. In total, 55 patients with spastic cerebral palsy were enrolled in the present study. Reliability by internal consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 14 publications
0
5
1
Order By: Relevance
“…These findings suggested that this characteristic of SMC-that the distal joint is more impaired than the proximal joint-does not change with age. On the other hand, the SCALE scores for each joint were lower than those reported in previous studies 2,7,14) . The SCALE scores for each joint in adults with CP were approximately 0.2 points lower than the SCALE scores reported in the previous study on children with CP.…”
Section: Discussioncontrasting
confidence: 87%
See 1 more Smart Citation
“…These findings suggested that this characteristic of SMC-that the distal joint is more impaired than the proximal joint-does not change with age. On the other hand, the SCALE scores for each joint were lower than those reported in previous studies 2,7,14) . The SCALE scores for each joint in adults with CP were approximately 0.2 points lower than the SCALE scores reported in the previous study on children with CP.…”
Section: Discussioncontrasting
confidence: 87%
“…SMC was assessed using the Selective Control Assessment of the Lower Extremity (SCALE) 2,14) . The participants were asked to perform the following movement patterns for 3 seconds each: (1) hip flexion and extension with the knee extended, (2) knee extension and flexion, (3) ankle dorsiflexion and plantarflexion with the knee extended, (4) subtalar inversion and eversion, and (5) toe flexion and extension.…”
Section: Participants and Methodsmentioning
confidence: 99%
“…The relationships with comparator measures were also weaker than those observed in other lower extremity studies. Although other studies using clinical lower extremity SVMC assessments such as the selective motor control scale or the SCALE found relationships with gross motor function [ 6 , 8 , 16 , 17 , 31 ], the assessgame outcomes did not correlate with the GMFCS level or the SCALE. We expect that this is caused by the differences between the assessgame and clinical assessments of SVMC.…”
Section: Discussionmentioning
confidence: 71%
“…These IPS parameters show the ability of dynamic balance to move COP within BOS. Spastic CP patients with diplegia have difficulty controlling selective voluntary movements 8) . Therefore, patients with CP often have insufficient motor control of the lower limbs that allow stabilization and balance while standing.…”
Section: Discussionmentioning
confidence: 99%